1968
DOI: 10.1115/1.3601197
|View full text |Cite
|
Sign up to set email alerts
|

On the Unstable Vibrations of a Shaft With Unsymmetrical Stiffness Carrying an Unsymmetrical Rotor

Abstract: In a rotating shaft system carrying an unsymmetrical rotor, or in a rotating shaft system with inequality in stiffness, there are unstable regions in the neighborhood of both the major critical speed ωc and the rotating speed ωd at which the sum of two natural frequencies of the system is equal to twice the rotating speed of the shaft. The unstable vibrations appearing in these unstable regions are treated for the system consisting of a rotor with unsymmetrical inertia and a shaft with unequal stiffness which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The dynamics of asymmetric rotors has been the subject of interest for several decades and many papers were published on this, to name a few by Brosens and Crandall [1], Yamamoto and Ota [2,3], and Arday"o and Frohrib [4]. Yuan Kang et al [5] utilizing "nite element formulation generalized the previous works to accommodate the asymmetry e!ects.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of asymmetric rotors has been the subject of interest for several decades and many papers were published on this, to name a few by Brosens and Crandall [1], Yamamoto and Ota [2,3], and Arday"o and Frohrib [4]. Yuan Kang et al [5] utilizing "nite element formulation generalized the previous works to accommodate the asymmetry e!ects.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a series of in-depth theoretical and experimental studies on the unstable vibrations of a rotating shaft carrying an unsymmetrical rotor were carried out by Yamamoto et.al. [3] [4]. Ardayfio and Frohrib [5] extended the four degree-of-freedom rotor system of Yamamoto and Ota [3] to include flexibility in the bearing supports.…”
Section: Introductionmentioning
confidence: 97%
“…Yamamoto and Ota (1964) showed that a rotating shaft system carrying unsymmetrical rotor experiences instability in the neighborhood of rotating speeds when the sum of the two natural frequencies of the system is equal to twice the rotating speed. Later, Yamamoto et al (1968) examined the unstable vibration of a system consisting of a rotor with unsymmetrical inertia, supported by rotating flexible shaft with unequal stiffness. Ardayfio and Frohrib (1976) examined instabilities of an asymmetric rotor with asymmetric shaft mounted on symmetric elastic supports.…”
Section: Introductionmentioning
confidence: 99%